Answer:
In assumption, x is the smaller even integer and x+2 is the next so it will be larger.
The integers are 4 and 6
Explanation:
Let the two consecutive even integers be x and x+2
Here x is the smaller even integer and x+2 is the next so it will be larger.
Now according to the given statement
Sum of both:
![x+x+2](https://img.qammunity.org/2021/formulas/mathematics/high-school/li1bxildjgq5j4vlbejpq1ax2fvyqk8bpj.png)
difference of 3 times the larger & 2 times the smaller:
![3(x+2)-2x](https://img.qammunity.org/2021/formulas/mathematics/high-school/as80506y2f0j3a4yhkd9hcqfelskdfkw13.png)
Putting the sum and difference equal:
![x+x+2 = 3(x+2)-2x](https://img.qammunity.org/2021/formulas/mathematics/high-school/cos8dxtzeqkpsfgb8ll11c2jg3z5qui8gn.png)
Solving the equation
![2x+2 = 3x+6-2x\\2x+2 = x+6\\2x+2-x = x+6-x\\x+2 = 6\\x+2-2 = 6-2\\x = 4](https://img.qammunity.org/2021/formulas/mathematics/high-school/zwo5tl6zwr7ywhwokz8iau9stjnttp81pa.png)
The next integer will be:
![x+2 = 4+2 = 6](https://img.qammunity.org/2021/formulas/mathematics/high-school/vzx6q2k9utx6nzso4vxonykijdoquebp5j.png)
Hence,
In assumption, x is the smaller even integer and x+2 is the next so it will be larger.
The integers are 4 and 6.